Solve the following system using the elimination method: 2x-4y=2 -4x+6y=-4
![Solve the following system using the elimination method 2x4y2 4x6y4 class=](https://us-static.z-dn.net/files/d65/79161ca675d1d5e036a9b3e32e7b269e.png)
Answer:
(1, 0)
Step-by-step explanation:
Given the 2 equations
2x - 4y = 2 → (1)
- 4x + 6y = - 4 → (2)
Multiplying (1) by 2 and adding to (2) will eliminate the x- term
4x - 8y = 4 → (3)
Add (2) and (3) term by term
(- 4x + 4x) + (6y - 8y) = (- 4 + 4), simplifying gives
- 2y = 0 ⇒ y = 0
Substitute y = 0 in (1) or (2)
Substituting in (1) gives
2x - 0 = 2, that is
2x = 2 ( divide both sides by 2 )
x = 1
Solution is (1, 0 )